2000
DOI: 10.1054/bjoc.2000.1479
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism of the interleukin-1 β gene influences survival in pancreatic cancer

Abstract: Pro-inflammatory cytokines contribute to the cachexia associated with pancreatic cancer and stimulate the acute phase response which has been associated with shortened survival in such patients. Polymorphisms of cytokine genes may influence their production. The present study examined the effect of a polymorphism of the interleukin (IL)-1b gene upon the inflammatory state and survival in pancreatic cancer. Genomic DNA was obtained from 64 patients with pancreatic cancer and 101 healthy controls. Using the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 23 publications
0
51
4
Order By: Relevance
“…None significant correlation was found with PDAC and IPMN cases. Although Barber et al [36] , reported that the +3954 C/T polymorphism of the IL-1β gene predisposes to pancreatic cancer; our findings did not reveal any significant association. Additionally, they are partly in agreement with the findings of Cigrovski Berkovic et al [37] , which suggest that there is an association between the IL-1β 511 C/T genotype and the susceptibility to pNET, especially functional pNETs.…”
Section: Discussioncontrasting
confidence: 99%
“…None significant correlation was found with PDAC and IPMN cases. Although Barber et al [36] , reported that the +3954 C/T polymorphism of the IL-1β gene predisposes to pancreatic cancer; our findings did not reveal any significant association. Additionally, they are partly in agreement with the findings of Cigrovski Berkovic et al [37] , which suggest that there is an association between the IL-1β 511 C/T genotype and the susceptibility to pNET, especially functional pNETs.…”
Section: Discussioncontrasting
confidence: 99%
“…The distribution of IL-1bþ3953, IL-1b-511 and IL-1RA polymorphism in a control population is presented in Table II, together with Japanese 25,26 and Caucasian 3,7,8,15 data, which have been previously reported. The polymorphism frequency in our study was within the Hardy-Weinberg equilibrium.…”
Section: Polymorphisms Of Il-1b and Il-1ra In The Control Populationmentioning
confidence: 89%
“…4 Barber et al reported that the serum level of IL-1b is higher in the genotype IL-1bþ3953 T/T. 7 Thus, it may be through IL-1b-mediated inflammation and hypochlorhydria that the cancer risk in the gastric corpus is higher in the genotype IL-1bþ3953 C/T in Japanese. The fact seemed to be in contrast to the reports of El-Omar et al, who found no difference in the groups defined by the location of the carcinoma (corpus and antrum).…”
Section: Table III -Frequencies and Adjusted Odds Ratios (Or) Of 1l-1mentioning
confidence: 99%
See 1 more Smart Citation
“…One recent case-control study in China examined the association between lung cancer and IL1B C3954T (14); although results were negative, the study was limited by low statistical power (n = 119 cases). The IL1B C3954T polymorphism has been associated with risk of cervical dysplasia (32) and mortality after pancreatic cancer diagnosis (33). Some studies also found this polymorphism associated with risk of gastric cancer (34).…”
Section: Discussionmentioning
confidence: 99%